Towards personalistic psychology - Uchnast, Zenon (Studia Psychologica: Theoria et praxis, 2002)
In 1990s the Institute for Personalist Psychology (IPP) was founded at the Franciscan University of Steubenville (USA), with James DuBois, assistant professor at the International Academy of Philosophy in Liechtenstein, as the first director. This inspiring international initiative has some frame of references in the person-centered approaches of William Stern, Gordon Allport, and Rollo May. Special attention is drawn to the following list of ten philosophical principles of IPP: The nature of evidence, human beings as personal beings, the spiritual dimension of human persons, the objectivity of value, rationality, human freedom, moral responsibility, the religious dimension, the limitations of human persons, society and the family.